An empirical study of accounting software acceptance among Bengkulu City students - Sriwidharmanely; Vina Syafrudin (FEP, 2012)
The objective of the study was to analyse the acceptance of the accounting software by accounting students using the Technology Acceptance Model (TAM). The results of this research were generated using the variables - the perceived ease of use, the perceived usefulness, the attitude towards using, the behavioural intention to use, and the actual system usage. These variables were analysed using the Structural Equation Model (SEM). The samples of this research were 162 accounting students who were able to operate accounting software (such as MYOB and GL) at Bengkulu City, Bengkulu Province, Indonesia. The results show that the perceived ease of use had a positive significant effect on the perceived usefulness, while the perceived usefulness had a positive significant effect on the behavioural intention to use and the behavioural intention to use had a positive significant effect on the actual system usage of the accounting software.